Attitudes, beliefs, and knowledge regarding medical cannabis among healthcare students in the Republic of Cyprus: a cross-sectional descriptive correlational study - Sokratous, Sokratis; Mpouzika, Meropi; Kaikoushi, Katerina; Alexandrou, George; Karanikola, Maria (Frontiers in Psychiatry, 2023)
Background: There is a lack of evidence concerning healthcare students’ education on medical cannabis (MC). We explored healthcare students’ attitudes, beliefs, and knowledge regarding the use of MC. We paid special attention to differences across sociodemographic and educational characteristics. Methods: A descriptive cross-sectional study (November 2019- March 2020) was applied in undergraduate and postgraduate healthcare students (nurses, physiotherapists, speech therapists, pharmacists, and occupational therapists) in the Republic of Cyprus (response rate = 91%). We used the Medical Cannabis Questionnaire (MCQ) to collect data on the attitudes and knowledge on MC use. Descriptive and inferential statistics were applied and Pearson’s chi-square test was used to assess group differences. Results: Most of participants had a positive attitude toward MC. Statistically significant differences were observed between genders in terms of beliefs/risk associated with the use of MC, with males being more likely to believe that there are significant mental-health benefits associated with using ΜC (x2 = 8.06, OR: 0.6s, 95% CI: 0.49–0.89) and females being more likely to believe that using MC poses serious physical- (x2 = 23.00, OR: 1.6, 95% CI: 1.35–2.0, p < .001) and mental-health (x2 = 13.06, OR: 1.4, 95% CI: 1.2–1.81) risks. Moreover, participants who received formal education about MC during their study/training were more prepared to answer patient/client questions about ΜC (x2 = 17.27, df = 1, p < .001). In addition, participants who received formal education had more friends (x2=12.69, df=1, p <.001) or family members who used MC (x2=4.03, df=1, p <.05). Conclusions: This study provides useful information for curriculum development, educational changes, and policy decisions related to cannabis use for medical purposes in Cyprus. The results showed that the majority of the healthcare students who participated in the study favored MC use. However, the participants reported a lack of knowledge and recommended additional evidence-based research and education to enhance their knowledge about MC use. Therefore, we recommend the implementation of formal education on MC among healthcare students in the Republic of Cyprus during their study and clinical training. Furthermore, it is important to include MC-related theoretical and clinical/laboratory courses during studies and clinical practice.